Extending the Wharton Map: Historical Continuity in Edith Wharton’s Osprey Notes (1926) - Kovács, Ágnes Zsófia (AMERICANA E-journal of American Studies in Hungary, 2019)
This essay places Wharton manuscript travel notes of her 1926 Aegean cruise titled Osprey Notes in the context of Wharton’s other travel writing and, simultaneously, maps out some of the intellectual influences that shaped the views represented in it. The theme of historical continuity as an experience to be reconstructed or even as a voice to be listened to appears in earlier travel pieces by Wharton. For Wharton the problem of understanding the past is strongly influenced by work of art historians: especially John Ruskin, Charles Eliot Norton, and Bernard Berenson. The essay explores how historical continuity familiar from other travel texts by Wharton is represented in the Notes, and if or how the influences of Ruskin, Norton, or Berenson are present in the Greek fragments. The aim is to map the traditions of writing and seeing that saturate Wharton’s accounts of classical Greek sites. The article argues that Wharton’s late travel notes are strongly linked to her earliest pieces both thematically through the concern with views, landscapes, ruins and the presence of the past and rhetorically through her method of Ruskinian observation and description.